Analisis Faktor-Faktor Yang Mempengaruhi Konsumsi Marjinal Sumatera Utara Dalam Perspektif Ekonomi Islam - Rafi Faizin; Imsar Imsar; Aqwa Naser Daulay (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study analyzes the number of MPC of North Sumatra in 2006-2023 and the short-term and long-term relationship between the variables of GRDP, Inflation and Zakat. Everyone is always related to consumption to meet the needs of food, clothing, entertainment or for other needs. The level of consumption depends on people's income. This research uses Keyness theory by using existing formulas. The type of data used is secondary data sourced from BPS (Central Bureau of Statistics) and Baznas, namely data from 2006-2023. This study uses a cointegration test which is one of the tests of the VAR VECM method to determine whether or not there is short-term and long-term influence. The data used used time series data from 2006-2023 with annual data. The results show that the MPC value of North Sumatra from 2007 to 2023 is not stable and does not show a decreasing number when income increases. in the short term, Inflation on lag 1 (+) has a significant effect as well as inflation. And zakat on lag 1 (-) on consumption in North Sumatra. In the long run, GRDP in lag 1 is -1.21791 which is smaller than 1.99546 which shows negative results in the long run. Likewise, Inflation and Zakat variables have a negative effect.